2023
DOI: 10.2147/ijn.s400610
|View full text |Cite
|
Sign up to set email alerts
|

Development and Optimization of Imiquimod-Loaded Nanostructured Lipid Carriers Using a Hybrid Design of Experiments Approach

Abstract: Background Imiquimod (IMQ) is an immunomodulating drug that is approved for the treatment of superficial basal cell carcinoma, actinic keratosis, external genital warts and perianal warts. However, IMQ cream (Aldara ® ) has several drawbacks including poor skin permeation, local toxicity, and compromised patient compliance as a topical pharmacological option. Methods Our research aimed to develop and optimize nanostructured lipid carriers (NLC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 66 publications
(109 reference statements)
1
5
0
Order By: Relevance
“…High surfactant concentration was illustrated to decrease surface tension, thereby stabilising the surface during homogenisation and preventing particle agglomeration which in turn leads to the production of smaller particle size [ 60 , 61 ]. Kim et al [ 58 ] and Taha et al [ 62 ] also reported similar findings. Sonication time showed biphasic responses indicating optimal sonication time was required to produce particles of the desired size as illustrated in Fig.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…High surfactant concentration was illustrated to decrease surface tension, thereby stabilising the surface during homogenisation and preventing particle agglomeration which in turn leads to the production of smaller particle size [ 60 , 61 ]. Kim et al [ 58 ] and Taha et al [ 62 ] also reported similar findings. Sonication time showed biphasic responses indicating optimal sonication time was required to produce particles of the desired size as illustrated in Fig.…”
Section: Resultssupporting
confidence: 60%
“…The positive effect of the total lipid on the size of the nanoparticles could be due to the increase in the viscosity of the formulation that in turn reduces the effectiveness of particle-breaking (sonication) processes [ 57 ]. The increased particle size with the increase in the amount of total lipid could also be attributed to other reasons such as aggregation between lipid particles, increased chances of collision as well as inadequate surfactant amount to cover the lipid particle’s surface [ 58 ]. The finding agrees with the work of Kim et al where NLCs of imiquimod with higher lipid concentration resulted in larger particle size.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the 5-FU content found in the SC was much higher from the cream formulation (62.78 ± 18.9 µg/cm 2 ) compared to the Patch-CONT (24.47 ± 13.6 µg/cm 2 ), Patch-TRAN (11.33 ± 3.1 µg/cm 2 ) and Patch-OA (28.34 ± 12.5 µg/cm 2 ). This may indicate that the 5-FU from the commercial formulation was not effectively partitioned out from the SC and penetration into the deeper tissues as a target site where more invasive NMSC grows [ 34 , 35 ]. Whilst the patch formulations did not show a statistically significant difference in epidermis and dermis deposition, Patch-TRAN (76.39 ± 27.7 µg/cm 2 ) and Patch-OA (82.56 ± 8.2 µg/cm 2 ) demonstrated much deeper penetration, as indicated in the 5-FU recovery from the receptor chamber than Efudix ® cream (34.63 ± 8.3 µg/cm 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The first step was to review the IMQ solubility data reported in the literature for the solvents considered ( Table 1 ) [ 4 , 6 , 7 , 8 , 9 ]. Table S1 reports the solubility values for all the other solvents cited in the literature [ 4 , 6 , 7 , 8 , 9 , 10 , 11 ].…”
Section: Literature Reviewmentioning
confidence: 99%